2022
DOI: 10.1158/1078-0432.ccr-22-1386
|View full text |Cite
|
Sign up to set email alerts
|

Mass Cytometry Reveals Classical Monocytes, NK Cells, and ICOS+ CD4+ T Cells Associated with Pembrolizumab Efficacy in Patients with Lung Cancer

Abstract: Purpose: Immune checkpoint inhibitors (ICI) have revolutionized the treatment of non-small cell lung cancer (NSCLC), but predictive biomarkers of their efficacy are imperfect. The primary objective is to evaluate circulating immune predictors of pembrolizumab efficacy in advanced NSCLC patients. Experimental Design: We use high-dimensional mass cytometry (CyTOF) in baseline blood samples of advanced NSCLC patients treated with pembrolizumab. CyTOF data are analyzed by machine-learning algorithms (Citrus, tSNE)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…Again, we showed that NK cells were, indeed, key effector cytotoxic cells that were associated to high myeloid diversity and increased monocytic cells [ 45 ]. A recent study corroborated the predictive power of CD4 T cells, NK cells and monocytes in a cohort of patients from the seminal KEYNOTE-001 study [ 157 ]. The application of multi-parametric flow cytometry highlighted the elevation of PD-1, PD-L1 and PD-L1 in T cells as biomarkers of worse survival [ 179 ].…”
Section: Systemic Cd4 Immunity As a Biomarker Of Response To Pd-l1/pd...mentioning
confidence: 65%
See 1 more Smart Citation
“…Again, we showed that NK cells were, indeed, key effector cytotoxic cells that were associated to high myeloid diversity and increased monocytic cells [ 45 ]. A recent study corroborated the predictive power of CD4 T cells, NK cells and monocytes in a cohort of patients from the seminal KEYNOTE-001 study [ 157 ]. The application of multi-parametric flow cytometry highlighted the elevation of PD-1, PD-L1 and PD-L1 in T cells as biomarkers of worse survival [ 179 ].…”
Section: Systemic Cd4 Immunity As a Biomarker Of Response To Pd-l1/pd...mentioning
confidence: 65%
“…The study by Kagamu and collaborators, together with our study, provides strong evidence that functional CD4 immunity is needed to achieve efficacious clinical responses in NSCLC [ 48 ]. While this manuscript was in revision, another study corroborated the utility of systemic CD4 T cell quantification as a biomarker of response to immunotherapy in patients from the landmark study KEYNOTE-001 [ 157 ].…”
Section: Cd4 Immunity In Pd-l1/pd-1 Blockade Immunotherapymentioning
confidence: 81%
“…Emerging literature reports that ICOS or ICOSL is dysregulated in various cancer types and contributes to tumor immune escape. 10 This study explored ICOS and ICOSL expression and their correlation with clinical outcomes in human NSCLC using TCGA data mining; also immunohistochemistry analysis was performed using freshly resected tumor tissue from selected lung cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the antitumor effect of the ICOS/ICOSL pathway has been recognized. Emerging literature reports that ICOS or ICOSL is dysregulated in various cancer types and contributes to tumor immune escape 10 . ICOS/ICOSL expressed in regulatory T‐cells (Tregs) within the tumor microenvironment largely influences T‐cell‐mediated tumor immune tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Having said that, CyTOF technology is still a valid and outstanding tool. Indeed, Rochigneux et al performed a high-dimensional mass cytometry examination of peripheral blood mononuclear cells (PBMCs) from NSCLC patients treated with pembrolizumab prior to start the treatment ( 13 ). The authors provided evidence that the blood baseline frequencies of classical monocytes, natural killer (NK) cells and inducible T-cell costimulatory ICOS + CD4 + T-cells were associated with pembrolizumab efficacy.…”
mentioning
confidence: 99%